Why do bigger countries have more problems with the Stability and Growth Pact? - Bodo Herzog (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2005)
The European Fiscal Framework and the Stability and Growth Pact (SGP) have had great significance since the completion of the European Monetary Union (EMU) in 1999. The current enforcement and credibility problems, and discussion about reforming the SGP, as well as the failure to impose sanctions and early warnings against states in breach of the Pact, have introduced a new subject for economic research. One of the most surprising observations in recent years is that the larger countries in the EMU have more problems with the budget thresholds in the SGP than the smaller countries. To explain this 'stylized fact' we solve a model of 'rational' delay in consolidation and relate it to several economic and political variables. The model shows that larger governments tend to prefer slower consolidation because they are not concerned about the risk of breaching the SGP and face less output volatility. Moreover we solve in the theoretical model one unexplored phenomenon in empirical macroeconomics: why does larger government size imply less macroeconomic volatility? We demonstrate this approach and its results with current empirical data on the performance of the EMU and the SGP.
Keywords: E60; F33; F30; 330; Monetary Union; Fiscal Policy; Stability and Growth Pact; EU-Stabilitätspakt; Haushaltskonsolidierung; Finanzpolitik; Landesgrösse; Makroökonomischer Einfluss; Volatilität; EU-Staaten